Expert Evaluation of a Developed CBT Package for Upper Basic School Student in Civic Education in Ilori - Charles Olubode Olumorin,; Amos Ochayi Onojah,; Ibrahim Idowu Jimoh,; Adenike Aderogba Onojah, (JELM, 2023)
Innovative assessments that allow students to manipulate data and role play are currently being produced using the CBT method. But when not properly designed, students could lose their interest in adopting it. This study ascertained expert’ evaluation of a developed civic education CBT package for upper basic school student in Civic Education in Ilorin. Specifically, the study (i) determined the process in using the designed CBT Package to process real time result and valid test score, & (ii) evaluate the rating of experts on the developed Civic education CBT package for upper basic school student. This study adopted the Research and Development type and Descriptive type while 120 civic education teachers and lecturers in related discipline evaluated the developed CBT system. Findings established that experts rate the designed CBT system to be very good and was highly recommended. The study concluded that the designed CBT is effective, which implies that it can be adopted for assessment in upper basic school. It was thus recommended that the curriculum developer should also add this CBT system to the curriculum as a mode of assessment for upper basic school